Optical Coherence Tomography-Based Scattering Properties of Retinal Vessels in Glaucoma Patients. (3rd April 2018) - Kromer, Robert; Boelefahr, Sebastian; Eck, Brendan; Rahman, Shafin; Klemm, Maren
ABSTRACT: Purpose : Clinical trials have demonstrated that retinal blood flow deficiencies are present in patients with open-angle glaucoma (OAG). We introduce a method for facilitating retinal vessel analysis: The intensity of the distal shadow of vessels in optical coherence tomography (OCT) caused by the scattered signal is analyzed, compared between healthy subjects and OAG patients and correlated with OCT angiography (OCT-A) flow density. Patients and Methods : We recruited 80 patients with diagnosed OAG (mean age 63.4 ± 13.2 years) and 80 healthy age-matched control subjects for comparison, and 20 patients for the correlation with OCT-A flow density. Patients received perimetry, peripapillary OCT measurements, and selected patients OCT-A of the papillary area. The vessel shadow intensity (VSI) is based on peripapillary OCT scans: the intensity of the distal vessel shadow was automatically compared to its surroundings, separated by arteries and veins. Flow density of the OCT-A scan was calculated by binarization and quantification of the pixel density. Results : The VSI for arteries was in OAG patients with 7.52 ± 2.62 [%] significantly lower compared to healthy subjects (9.03 ± 3.38 [%], p = 0.0029). In veins, the VSI was as well significantly lower for OAG patients (14.9 ± 3.59 [%]) compared to healthy subjects (17.46 ± 4.45 [%], p < 0.0001). Furthermore, in OAG patients there was a significant correlation of mean deviation of the visual field results with the veins' VSI ( p  = 0.0006; r  = −0, 454). There was no significant correlation of scattering properties with OCT-A flow density ( p  > 0.05). Conclusions : We conclude that the OCT-based analysis of the scattering properties of retinal vessels differs significantly between patients with OAG and healthy subjects. Furthermore, changes in the scattering properties of veins correlated with the stage of the disease in terms of visual field deficits. These properties might complement existing measurements of ocular blood flow including OCT-A flow density.